Study of Image Qualities From 6D Robot–Based CBCT Imaging System of Small Animal Irradiator. (December 2017) - Sharma, Sunil; Narayanasamy, Ganesh; Clarkson, Richard; Chao, Ming; Moros, Eduardo G.; Zhang, Xin; Yan, Yulong; Boerma, Marjan; Paudel, Nava; Morrill, Steven; Corry, Peter; Griffin, Robert J.
Purpose: To assess the quality of cone beam computed tomography images obtained by a robotic arm-based and image-guided small animal conformal radiation therapy device. Method and Materials: The small animal conformal radiation therapy device is equipped with a 40 to 225 kV X-ray tube mounted on a custom made gantry, a 1024 × 1024 pixels flat panel detector (200 μm resolution), a programmable 6 degrees of freedom robot for cone beam computed tomography imaging and conformal delivery of radiation doses. A series of 2-dimensional radiographic projection images were recorded in cone beam mode by placing and rotating microcomputed tomography phantoms on the "palm' of the robotic arm. Reconstructed images were studied for image quality (spatial resolution, image uniformity, computed tomography number linearity, voxel noise, and artifacts). Results: Geometric accuracy was measured to be 2% corresponding to 0.7 mm accuracy on a Shelley microcomputed tomography QA phantom. Qualitative resolution of reconstructed axial computed tomography slices using the resolution coils was within 200 μm. Quantitative spatial resolution was found to be 3.16 lp/mm. Uniformity of the system was measured within 34 Hounsfield unit on a QRM microcomputed tomography water phantom. Computed tomography numbers measured using the linearity plate were linear with material density ( R 2 > 0.995). Cone beam computed tomography images of the QRM multidisk phantom had minimal artifacts. Conclusion: Results showed that the small animal conformal radiation therapy device is capable of producing high-quality cone beam computed tomography images for precise and conformal small animal dose delivery. With its high-caliber imaging capabilities, the small animal conformal radiation therapy device is a powerful tool for small animal research.